How do you solve this for y? 1 – 2\3 y = 9\5 – y\5 + 3\5 1  2/3y = 9/5  y/5 + 3/5 15(1  2/3y = 9/5  y/5 + 3/5) {multiplied entire equation by common denominator, 15} 15(1)  15(2/3y) = 15(9/5)  15(y/5) + 15(3/5) {multiplied each term by 15} 15  10y = 27  3y + 9 {cancelled and multiplied} 15  10y = 36  3y {combined like terms} 15 = 36 + 7y {added 10y to both sides} 21 = 7y {subtracted 36 from both sides} y =  3 {divided both sides by 7}  Algebra House
0 Comments
Your comment will be posted after it is approved.
Leave a Reply. 
Examples
All
